THE ROADSHOW PROMOTION METHOD IN AN EFFORT TO INCREASE VISITS TO KAMPUNG BATU MALAKASARI - Putra, Reza Granada; Musafa, Musafa (Multifinance, 2023)
Bandung Regency has a variety of nature-based tourism options that can be found here, each of which has its own uniqueness from one place to another. In fact, if you look at its geographic location, Bandung City and Bandung Regency are indeed very strategically located, as this area is very close to the capital city of Jakarta, which makes Bandung City and Bandung Regency currently a tourist escape for some people, especially residents of the capital city of Jakarta. The method used in this research is a qualitative research method, and the results of this research show that there are several solutions to solving problems in Kampung Batu Malakasari to attract visitors to visit, namely the process of conveying information carried out by Kampung Batu Malakasari through a team. Marketing through offline promotions or pick-up and drop-off is to convince potential visitors to visit the Kampung Batu Malakasari tourist destination. Furthermore, by establishing cooperation between Kampung Batu Malakasari and schools, the selection of this promotion is in accordance with the main target of Kampung Batu Malakasari itself, so that information is more effective and efficient.